The Institutional Future of the European Union - Fabbrini, Sergio (2011)
The ink of the Lisbon Treaty‟s signatories was not yet dry before the financial crisis, which took a serious turn for the worse in 2010, called that Treaty into question. The financial bankruptcy of Greece and Ireland and the serious financial difficulties of Portugal and Spain have, in fact, determined the need for us to reconsider the “EU institutional arrangement”, which was so painstakingly constructed in the course of the first decade of the century. Under the pressure, on one hand, of domestic electoral and constitutional constraints and, on the other, of the financial threat of the collapse of the euro, the EU heads of state and government have finally ended up radically reforming the EU system of economic governance. At the crucial European Council held on 24-25 March 2011, fundamental decisions were adopted, such as: the reinforcement of macroeconomic surveillance, the strengthening of the stability and growth pact, a corrective mechanism for macroeconomic imbalances, the European semester, the Euro Plus pact and the European Stability Mechanism (ESM). This new economic governance system mainly concerns the EU member states who have adopted the euro. The most striking of these innovations, the ESM, implies the establishment of a new treaty by the euro-area member states “as an intergovernmental organisation under public international law”, a treaty located outside the EU‟s institutional framework, though justified by a proposal of an amendment to Article 136 of the TFEU. Are these decisions a challenge to the integrity of the treaty-based system of the EU or do they represent a radical step forward in the integration process? This paper tries to answer this question, with a critical discussion of the two main paradigms interpreting the EU (the sui generis and the parliamentary options). It reaches the conclusion that those paradigms are unsatisfactory for explaining those decisions, thus proposing a new paradigm, defined as unionist, for interpreting the latter and fine-tuning their implications.